Comparing the effects of two proprioceptive neuromuscular facilitation stretching techniques and static stretching on active knee extension range of motion and vertical jump performance - Vaillant, Nick (My University, 2018)
Proprioceptive neuromuscular facilitation (PNF) stretching has often been identified as an effective stretching technique for improving range of motion (ROM) prior to exercise. The two PNF stretching techniques that are most commonly performed are autogenic inhibition and reciprocal inhibition stretching. These techniques increase ROM by applying resistance to either agonist (i.e. autogenic) or antagonist (i.e. reciprocal) muscle groups to reduce reflex activity. Variability in PNF stretching procedures, however, cause difficulty comparing studies and translating findings to clinical practice. Limited research has also been performed on the effects of PNF stretching on athletic performance. The present study compared the effects of static, autogenic inhibition, and reciprocal inhibition stretching on knee extension ROM and vertical jump performance. Thirty healthy participants (16 male and 14 female) performed an Active Knee Extension test and a Vertical Jump test after 4 counter balanced stretching conditions. The stretching conditions consisted of no stretching (control), static stretching, autogenic inhibition stretching, and reciprocal inhibition stretching. A one-way analysis of variance (ANOVA) with repeated measures and the Bonferonni post hoc test identified static stretching, autogenic inhibition stretching, and reciprocal inhibition stretching significantly increased knee extension ROM by means of 7.8, 8.1, and 9.4 degrees, respectively when compared to no stretching (p<.001). No significant differences were identified between the ROM increases associated with each technique (p>0.05). Pairwise comparisons also identified no significant differences in vertical jump height (cm) before or after the use of static, autogenic inhibition, or reciprocal inhibition stretching (p>0.05). The present study was the first to compare these stretching techniques using recommended pre-activity procedures. The results of this study identified all three stretching techniques as effective techniques for improving ROM prior to exercise without decreasing vertical jump performance.
Keywords: Proprioceptive neuromuscular facilitation; Stretching; Range of motion; Vertical jump; Autogenic inhibition; Reciprocal inhibition